Rozważania na temat represyjnych i prewencyjnych elementów odpowiedzialności odszkodowawczej na przykładzie instytucji odszkodowania karnego (punitive damages) w świetle orzeczenia Sądu Najwyższego oraz Trybunału Konstytucyjnego - Kochanowski, Maciej (Studia Prawa Publicznego, 2019)
The verdict of the Supreme Court of 11 October 2013 (fi le I CSK 697/12) and the decision of the Constitutional Tribunal of 25 June 2015 (fi le SK 32/14) are discussed and their signifi cance for the understanding of punitive damages analysed. The main problem discussed in this paper is the question whether there is room under Polish law for punitive damages modelled a common law system and whether the adoption of this solution could possibly infl uence the basic premises constituting the liability for damages already adopted. The main focus has been put on the argumentation of the Supreme Court presented in its verdict regarding the possibility of enforcing by Polish courts a judgment in which a foreign court awarded punitive damages, and the arguments of the Constitutional Tribunal regarding the constitutionality of a legal provision establishing a possibility of fl at-rate damages, being awarded and increased in the event of the determination of guilt by the breaching party. Certain detailed provisions that are contradictory from the point of view of the fundamental assumptions underlying the liability for damages in Polish law and the laws of most European legal systems (and the German system in particular) are also examined. Further, a synthetic analysis of the positive and negative aspects of punitive damages identifi ed by other researchers is presented. This is followed by a mention of other institutions available under Polish law which may constitute an alternative to punitive damages, at least when it comes to the provision of an adequate preventive and punitive measure in the event of gross or culpable damage.